Management perspective for transport telematics : 18th International Conference on Transport System Telematics, TST 2018, Krakow, Poland, March 20-23, 2018, Selected Papers /: 18th International Conference on Transport System Telematics, TST 2018, Krakow, Poland, March 20-23, 2018, Selected Papers. (2018) - Unknown
No abstract available